Global burden of HIV among men who engage in transactional sex: a systematic review and meta-analysis - Oldenburg, Catherine; Bärnighausen, Till; Mayer, Kenneth H. (PLOS ONE, 2014)
Background Men who engage in transactional sex, the exchange of sex for money, goods, or other items of value, are thought to be at increased risk of HIV, but there have been no systematic attempts to characterize HIV burden in this population. We undertook a systematic review and meta-analysis to quantify the burden in this population compared with that of men in the general population to better inform future HIV prevention efforts. Methods We searched seven electronic databases, national surveillance reports, and conference abstracts for studies of men who engage in transactional sex published between 2004-2013. Random effects meta-analysis was used to determine pooled HIV prevalence and prevalence ratios (PR) for the difference in HIV prevalence among men who engage in transactional sex as compared to general population men. Findings Of 66 studies included representing 31,924 men who had engaged in transactional sex in 28 countries, pooled biological assay-confirmed HIV prevalence was 10.5% (95% CI = 9.4 to 11.5%). The highest pooled HIV prevalence was in Sub-Saharan Africa (31.5%, 95% CI = 21.6 to 41.5%), followed by Latin America (19.3%, 95% CI = 15.5 to 23.1%), North America (16.6%, 95% CI = 3.7 to 29.5%), and Europe (12.2%, 95% CI = 6.0 to 17.2%). Men who engaged in transactional sex had an elevated burden of HIV compared to the general male population (PR = 20.7, 95% CI = 16.8 to 25.5). Conclusions The global burden of HIV is disproportionately high among men who engage in transactional sex compared with the general male population. There is an urgent need to include this population in systematic surveillance as well as to scale-up access to quality HIV prevention programs.